Design and Development of Interactive E-Book Learning Media Using Heyzine Flipbook on Prayer Materials: A Study of Validity, Practicality, and Effectiveness - Velia Khoirunisah, Intan; Rohman, Miftahur (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2025)
This study aims to develop interactive e-book learning media based on Heyzine Flipbook on prayer materials and to examine its validity, practicality, and effectiveness. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Expert validation results indicated that the media was categorized as highly valid. Practicality testing through teacher and student responses demonstrated that the media was highly practical. Furthermore, the effectiveness test based on learning outcomes showed a significant improvement, indicating that the media was effective in Islamic Religious Education learning. Therefore, Heyzine Flipbook can serve as an innovative alternative medium to enhance students’ understanding and skills in performing prayer.